Transformation of BUMDes Towards Sustainable Agroindustry: Smart Greenhouse and Tower Hydroponics System Approach in Organic Farming Practices - Nur Anita Yunikawati; Dwi Wulandari; Putra Hilmi Prayitno; Fuad Indra Kuusuma; Ari Gunawan; Afis Baghiz Syafruddin; Widia Ayu Wulandari (CV RIFAINSTITUT, 2025)
Organic farming has developed into a strategic solution to address food security issues, environmental degradation, and increasing public demand for healthy food products. The role of Village-Owned Enterprises (BUMDes) as drivers of the village economy is vital to building an innovative and sustainable agroindustry model. This study examines the transformation process of BUMDes in Wonokerso Village, located in Pakisaji District, Malang Regency, towards the development of an organic farming-based agroindustry ecosystem that utilizes the integration of Smart Greenhouse and Tower Hydroponics System (THS) technology. The results of the study indicate that the use of Smart Greenhouse and THS allows for more efficient utilization of narrower land. It also shows that organic farming results become more productive without relying on chemical pesticides. In addition, this technology helps more environmentally friendly farming practices and provides BUMDes with new opportunities for downstreaming agricultural products as part of local agroindustry development. In addition to technical aspects, this change is supported by an institutional approach. Here, BUMDes functions as an education facilitator and business incubator for organic farmers. This study suggests increasing the managerial capacity of BUMDes and village regulatory support to accelerate the sustainable transformation of green technology-based agroindustry. This occurs despite several challenges, such as limited technological literacy and access to capital